MBCL-32. SAFETY AND EFFICACY OF CONCURRENT CARBOPLATIN DURING CRANIOSPINAL IRRADIATION FOR HIGH-RISK/ MEDULLOBLASTOMA IN A RESOURCE-LIMITED SETTING. Issue 2 (22nd June 2018) - Gupta, Tejpal; Chinnaswamy, Girish; Sankaran, Hari; Vora, Tushar; Prasad, Maya; Epari, Sridhar; Sahay, Ayushi; Moiyadi, Aliasgar; Shetty, Prakash; Shirsat, Neelam; Krishnatry, Rahul; Sastri, GodaJayant; et al.
Abstract: PURPOSE: To review the safety and efficacy of concurrent carboplatin during craniospinal irradiation (CSI) in patients with high-risk/metastatic medulloblastoma. METHODS: Following surgery, patients with high-risk/metastatic medulloblastoma were treated with standard-dose CSI (35Gy/21 fractions) plus focal boost to primary site (19.8Gy/11 fractions) with concurrent carboplatin administered intravenously daily (30 mg/m 2 ) during the first 15 fractions of CSI. Prophylactic growth factors during concurrent phase were used as appropriate. All patients received six cycles of adjuvant systemic chemotherapy after completion of concurrent regimen. Worst toxicity during concurrent chemoradiotherapy was analyzed for safety, while progression-free survival (PFS) and overall survival (OS) were analyzed as measures of efficacy. RESULTS: A total of 94 patients (median age of 10 years) were included. Eighty-five (91.5%) patients completed the planned concurrent chemoradiotherapy regimen, with interruption of carboplatin dosing in only 9 (9.5%) patients. Grade 3 and 4 toxicities of concurrent carboplatin during CSI included thrombocytopenia (n=21, 22.3%), neutropenia (n=37, 39.3%), anemia (n=7, 7.4%), and nausea/vomiting (n=3, 3.2%). There were no toxic deaths during concurrent chemoradiotherapy. At a median follow-up of 31.8 months, the 3-year PFS for localized high-risk disease was significantly better at 76.8% (95%CI: 58.4-87.8%) compared to 51.9% (95% CI: 33.8-67.2%) for metastatic disease (p=0.006). Similar estimates for 3-year OS were 83.9% (95%CI: 67.4-92.5%) and 56.2% (95%CI: 38.3-70.7%) for localized high-risk and metastatic medulloblastoma respectively (p=0.048). CONCLUSION: Concurrent carboplatin during CSI results in acceptable rates of acute toxicity, but significantly improved disease-related outcomes in high-risk/metastatic medulloblastoma compared to historical data reported previously from developing countries.